Answers

2015-09-26T20:43:08+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Evaluating Algebraic Expressions.

3(8 + -2) - 2(8 - 8(-2))
PEMDAS
3(8−2)2(8−(8)(−2))
=(3)(6)2(8−(8)(−2))
=182(8−(8)(−2))
=18−2(8−(−16))
=18−(2)(24)
=18−48
=30                                          FINAL ANSWER

So, 3(x + y) - 2(x - 8y) when x is 8 and y is -2, the answer is -30. 

0
2015-09-26T20:59:07+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
  Solve for 3(x + y) - 2(x - 8y)  --  x = 8 , y = -2
 
     3(x + y) - 2(x - 8y)
 
     3[8 + (-2)] - 2[8 - 8(-2)]
 
     3(8 - 2) - 2(8 + 16)
 
     24 - 6 - 16 - 32
 
     18 - 48
 
     -30        

-----The answer is -30.

--

--Have a wanduhful evening =)
0